MSME Development Through Simple Bookkeeping, Financial Management and Internal Control Training - Mirna Wati; Laylan Syafina; Nurwani Nurwani (Quantitative Economics and Management Studies, 2024)
This research aims to develop MSMEs in Aek Songsongan Asahan Sub-district through training in simple bookkeeping, financial management, and internal control. This research uses a qualitative research design with a field study approach. Data were collected through interviews, observation, and evaluation. Data analysis used data triangulation, which combines data from various sources. The results showed that the training improved the efficiency and effectiveness of MSME operations, and promoted financial growth and stability. A more detailed discussion compares with previous studies in the last five years that show the positive impact of training in simple bookkeeping, financial management, and internal control on MSMEs. However, this study also explores aspects of sustainability and technology integration that have not been widely discussed in previous studies. This research makes an important contribution in developing MSMEs through human resource capacity building, particularly in the aspects of simple bookkeeping, financial management, and internal control.